Successful treatment of a Carbapenem-resistant Klebsiella pneumoniae carrying blaOXA-48, blaVIM-2, blaCMY-2 and blaSHV- with high dose combination of imipenem and amikacin. (2016) - Hajjej, Zied; Gharsallah, Hedi; Naija, Habiba; Boutiba, Ilhem; Labbene, Iheb; Ferjani, Mustapha
Abstract: We describe a case of 58-year-old man with septic shock due to Carbapenem-resistant Klebsiella pneumoniae (CR-Kp) bloodstream infections (BSI) who was successfully treated with a high dose association of amikacin and imipenem combined with continuous venovenous hemodiafiltration (CVVHDF). A Klebsiella pneumoniae (Kp) was isolated from the catheter culture and from two blood samples, drawn from the catheter before removal and from a peripheral vein. The Kp was intermediate to Amikacin (MIC = 16 μg/ml) and was resistant to all other antibiotics including Imipenem (MIC = 4 μg/ml), Colistin (MIC = 16 μg/ml) and Tigecycline (MIC = 4 μg/ml) according to the Clinical and Laboratory Standards Institute (CLSI) published in 2011. PCR amplification and sequencing verified the presence of blaOXA-48, blaVIM-2, blaCMY-2 and blaSHV-1 genes. Amikacin was given at a dose of 30 mg/kg (2.5 g) in a 30 min infusion and the dose of imipenem was increased to 1 g every 6 h despite patient's altered renal function (Creatinine Clearance = 25 ml/min). To avoid amikacin nephrotoxicity and to allow the use of high doses of imipenem, continuous venovenous hemodiafiltration (CVVHDF) (blood flow, 200 ml/h; dialysate, 1000 ml/h; ultrafiltrate, 2000 ml/h) was initiated 1 h after the start of the amikacin infusion and continued thereafter. The patient improved hemodynamically and norepinephrine was stopped five days after antibiotherapy adaptation.